1999
DOI: 10.1073/pnas.96.4.1779
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid induces oscillations in guard-cell cytosolic free calcium that involve phosphoinositide-specific phospholipase C

Abstract: Oscillations in cytosolic free Ca Stomata form pores in the epidermis of the leaf that allow CO 2 uptake for photosynthesis and water loss via transpiration. During drought, the loss of water through transpiration is reduced in response to an increase in the levels of the plant hormone abscisic acid (ABA) in the leaves (1). ABA stimulates the efflux of K ϩ from the guard cells that surround the stomatal pore, resulting in a reduction in guard-cell turgor and a decrease in the width of the pore (2). An increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
303
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(324 citation statements)
references
References 49 publications
18
303
2
1
Order By: Relevance
“…1), showing that the PP1/PP2A protein phosphatase inhibitors, okadaic acid and calyculin A, enhanced I Ca channel activity (Köhler and Blatt, 2002). In addition, phospholipids have been implicated in ABA-triggered cytosolic Ca 21 increases and stomatal closure (Staxen et al, 1999;Lemtiri-Chlieh et al, 2000). Treatment of epidermal strips with the phosphatidylinositol (PI)-3-kinase and PI-4-kinase inhibitors wortmannin and LY294002 inhibited PI kinase enzyme activities, enhanced stomatal opening, and impaired ABA-induced cytosolic Ca 21 increases, indicating that PI-3-P and PI-4-P modulate ABA signaling in guard cells (Jung et al, 2002).…”
Section: Ros and Aba Signalingmentioning
confidence: 99%
“…1), showing that the PP1/PP2A protein phosphatase inhibitors, okadaic acid and calyculin A, enhanced I Ca channel activity (Köhler and Blatt, 2002). In addition, phospholipids have been implicated in ABA-triggered cytosolic Ca 21 increases and stomatal closure (Staxen et al, 1999;Lemtiri-Chlieh et al, 2000). Treatment of epidermal strips with the phosphatidylinositol (PI)-3-kinase and PI-4-kinase inhibitors wortmannin and LY294002 inhibited PI kinase enzyme activities, enhanced stomatal opening, and impaired ABA-induced cytosolic Ca 21 increases, indicating that PI-3-P and PI-4-P modulate ABA signaling in guard cells (Jung et al, 2002).…”
Section: Ros and Aba Signalingmentioning
confidence: 99%
“…It should be noted that in other ABA-dependent responses that involve Ca 2ϩ , PI-PLC is not always implicated. For example, in broad bean, a total inhibition of ABA-induced stomatal closure requires both U73122 and nicotinamide, an inhibitor of cADPR synthesis (Jacob et al, 1999) whereas, in Commelina communis, treatment with U73122 is sufficient to inhibit ABA-induced cytosolic [Ca 2ϩ ] oscillations and stomatal closure (Staxen et al, 1999). Thus, it appears that different Ca 2ϩ channels may act in parallel or cooperate in ABA-signaling pathways according to the cell or the organ considered.…”
Section: Rab18 Expression In Arabidopsis Suspension Cellsmentioning
confidence: 99%
“…In the same species, it was demonstrated that an increase in PLC1 activity was necessary for the induction of the RD29a, KIN2, and RD22 ABAresponsive genes . In Commelina communis guard cells, Staxen et al (1999) have shown that U73122, an inhibitor of phosphatidylinositol-PLC (PI-PLC) activity, abolished ABAinduced cytosolic [Ca 2ϩ ] oscillations and stomatal closure.The involvement of phospholipase D (PLD) in ABA responses is better understood (Wang, 1999;Munnik, 2001 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Conversely, microinjection of the Ins(1,4,5)P 3 antagonist heparin 20 or reduction of Ins(1,4,5)P 3 production by inhibiting the activity or expression of PI-PLCs inhibits ABA-mediated signal transduction in guard cells. 21,22 Among the nine putative PI-PLC isoforms found in the Arabidopsis genome, 23,24 only PLC1 has been studied in depth, but not in guard cells. PLC1 is highly induced under dehydration and high salinity conditions 25 and is required for secondary responses to ABA signals.…”
Section: In Stomatal Openingmentioning
confidence: 99%